Rethinking Energy Security in Indonesia from a Net Zero Perspective - Muyasyaroh, Ayu Pratiwi (Indonesian Journal of Energy, 2024)
This study aims at examining in what way and to what extent Indonesia can safeguard its energy security from a net zero perspective. To achieve the objective of this study, the current and projected figures of three variables of the country’s energy system—the total emissions of Kyoto gases, CO2 emissions per sector, and primary energy mix—up to the end of the century were calculated. To shed light on these variables, IMAGE 3.2, an Integrated Assessment Model (IAM) was used. Three scenarios that include CurPol, NDC, and Glasgow were reviewed. This study found that the country's reliance on finite fossil fuels becomes unavoidable, potentially causing Indonesia to miss its net zero target while also being vulnerable to energy crises. It is found that neither strategy described in the country’s current policies nor in its NDC are in line with the country’s net-zero target.This situation is exacerbated by the fact that Indonesia has not enshrined its net zero target in law, leaving the country’s net zero commitment merely as a proposal rather than a pledge. Thus, if Indonesia is committed to ensure its energy security while also meeting its net zero target, it becomes imperative for the country to advance energy efficiency measures, incorporate carbon capture and storage (CCS) technology to control the emissions of ffossil fuels, and significantly increase the shares of renewables (solar and biomass in particular) to at least 50%in the country's primary energy mix.